Forest Watershed Management in the Southwestern United States - Gottfried, Gerald J; Ffolliott, Peter F; DeBano, Leonard F (Annals of Arid Zone, 2016)
Ponderosa pine and mixed conifer forested watersheds are the source of much of the surface water for theÂ· major river systems that support the cities, industries and farms of the arid southwestern United States. The need for sound watershed management was recognized during the early years of the 20th century. Research was initiated to determine the hydrology of forested watersheds and to provide land managers with information that could be used to design and implement treatments that benefited water augmentation and the production of other natural resources. A variety of experimental and current or potential silvicultural prescriptions were evaluated at locations throughout Arizona. While runoff augmentation is no longer the primary objective of forest management, research results provide guidance for forest watershed managers who are responsible for developing and implementing multi-resource prescriptions. The current emphasis for watershed management is to maintain and improve forest health and hydrologic function of watersheds. Welldesigned and implemented silvicultural.operations have a minor impact on the physical, chemical, and biological characteristics of stream water. Natural fire regimes have changed in the southwestern United States because of livestock grazing and aggressive fire suppression activities. The result has been an increase in fuels and stagnant stands, and an increase in large, severe, stand-replacing wildfires. Scientists are studying the role and impacts of fire as they attempt to restore more natural fire regimes in the forested ecosystems of the region.